Developmental processes in the Rosaceae through the lens of DNA and RNA methylation - Tamunonengiye Ofori, Lawson (2025)
The Rosaceae is a plant family of great importance for human nutrition and health. Many traits and developmental processes of the Rosaceae are influenced by epigenetic methylation, functions of which are now being unravelled in several important species of this family. Methylation of DNA at the 5th position of cytosine (5mC) is a well-established epigenetic mark that affects important cellular processes such as gene expression and genome stability and is involved in a wide range of plant biological functions. Further to this, recent technological advances have uncovered other naturally occurring chemical modifications of DNA and RNA as additional layers of regulatory epigenetic information in plants. In this review we give a comprehensive summary of plant 5-methylcytosine DNA methylation mechanisms and review their components identified in species of the Rosaceae family. We detail and discuss the role of 5mC DNA methylation dynamics in Rosaceae developmental processes, including phase transition, bud development, bud dormancy, plant architecture, plant regeneration, fruit development, ripening and senescence. We then review recent advances in understanding the newly identified nucleic acid modifications, N6-adenosine methylation of DNA (6mA) and RNA (m6A) as additional epigenetic mechanisms. We summarise identified components of adenosine methylation pathways in the Rosaceae and discuss the emerging roles of this modification in plant development including recent findings in Rosaceous species. Integrating epigenetic aspects of plant development with plant genetics and physiology is crucial for understanding biological processes in Rosaceous plants.